FORMASI VORTEX CURRENT PADA MODEL TERUMBU BUATAN - Emil Reppie; Daniel R. Monintja; M. Fedi A. Sondita; Indra Jaya; Victor P.H. Nikijuluw (Buletin PSP, 2006)
The present of an artificial reef on sea floor may lead to the creation of a vortex current or wake zone, and eddies on the downstream side of the reef. This wake zone could attract fish by providing shelter; turbulence at the edge of wake zone would attract pelagic species; and upwelled current and sediments or nutrients might also benefit certain pelagic species. However, there presently are insufficient data to suggest a universally valid relationship between habitat enhancement and the flow-reef-sediment interaction. The creation of vortex current on the sea bottom is difficult to observe, so it is usually conducted in a scaled-down experiment. This study was to determine the vortex current formation on the reef model and observed the response of fish samples at the different current velocities. A cubic reef type (12.5 cm) was placed in a water circulating tank. The measurement was made by running black colored particles; and the boundaries of downstream flow were determine by tracking the movement of each particle. Vortex current was clearly observed behind the reef model at the current velocity of about 34.75 cm/sec; and the fish tend to concentrate at the center or behind the reef model; but current weakens or vortex current disappear, fish were scattered.